Enhancement and prediction of modulus of elasticity of palm kernel shell concrete - Alengaram, Ubagaram Johnson; Mahmud, Hilmi; Jumaat, Mohd Zamin (Elsevier, 2011)
This paper presents results of an investigation conducted to enhance and predict the modulus of elasticity (MOE) of palm kernel shell concrete (PKSC). Scanning electron microscopic (SEM) analysis on palm kernel shell (PKS) was conducted. Further, the effect of varying sand and PKS contents and mineral admixtures (silica fume and fly ash) on compressive strength and MOE was investigated. The variables include water-to-binder (w/. b) and sand-to-cement (s/. c) ratios. Nine concrete mixes were prepared, and tests on static and dynamic moduli of elasticity and compressive strength were conducted. The SEM result showed presence of large number of micro-pores on PKS. The mineral admixtures uniformly filled the micro-pores on the outer surface of PKS. Further, the increase in sand content coupled with reduction in PKS content enhanced the compressive strength and static MOE: The highest MOE recorded in this investigation, 11kN/mm2, was twice that previously published. Moreover, the proposed equation based on CEB/FIP code formula appears to predict the MOE close to the experimental values.